Evaluation of sleep disorder in orthopedic trauma patients: a retrospective analysis of 1129 cases - Hai Yang; Yi-jia Liu; Jia-lu Ye; Li-hong Zhao; Ling-li Li; Xiao-ling Hou (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background In the trauma center wards, it is not unusual for patients to have sleep disorders, especially patients with an acute injury. Meanwhile, there is substantial evidence that sleep disorder is a predictor of depression and is an important feature of posttraumatic stress disorder. Methods All orthopedic trauma patients confined in a trauma ward in West China Hospital of Sichuan University between April 2018 and July 2019 were included in this retrospective study. Patients with mental impairment or craniocerebral injuries were excluded from the study. Basic demographic data and the Injury Severity Score (ISS) classification based on medical records were collected. The Pittsburgh sleep quality index (PSQI) was used to evaluate sleep quality, the visual analog scale (VAS) was used to evaluate physical pain, and the Barthel Index (BI) was used to evaluate activities of daily living (ADL). Univariate linear regression analysis and multivariate linear regression analysis were used to identify independently related factors. Results The average PSQI score was 6.3 (± 4.0). A total of 581 (51.4%) patients had a PSQI score > 5, indicating the presence of sleep disorders. The PSQI score was > 10 in 174 (15.4%) patients. Univariate statistical analysis showed that age, sex, education, ADL, and ISS classification were associated with increased PSQI scores. Marital status and pain were not associated with increased PSQI scores. When we used multivariate analysis to control for confounding variables, sex, ADL, and ISS classification remained independently associated with PSQI (P = 0.002, < 0.000, and 0.002, respectively). Conclusions In our study, sleep disorders were common (51.4% with PSQI > 5) and serious (15.4% with PSQI > 10) in patients with traumatic orthopedic injury. The following factors were closely associated with sleep disorders: sex, ADL, and ISS classification. Moreover, age and educational attainment have an independent impact on sleep quality. Unexpectedly, the VAS score for pain was not independently associated with the seriousness of sleep quality, which may be related to preemptive and multimodal analgesia. Further studies are required to clarify this ambiguity.